2022
DOI: 10.1093/pcp/pcac019
|View full text |Cite
|
Sign up to set email alerts
|

Tomato SlBES1.8 Influences Leaf Morphogenesis by Mediating Gibberellin Metabolism and Signaling

Abstract: Leaf morphogenetic activity determines its shape diversity. However, our knowledge to the regulatory mechanism in maintaining leaf morphogenetic capacity is still limited. In tomato, gibberellin (GA) negatively regulates leaf complexity by shortening the morphogenetic window. We here reported a tomato BRI1-EMS-SUPPRESSOR 1 (BES1) transcription factor, SlBES1.8, that promoted the simplification of leaf pattern in a similar manner as GA functions. OE-SlBES1.8 plants exhibited reduced sensibility to exogenous GA3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Already before the emergence of canonical GA signaling in vascular plants, DELLA proteins played a crucial role in plant development as seen in the liverwort Marchantia polymorpha, in which overexpression of MpDELLA leads to reduced plant growth (Hern andez-Garc ıa et al, 2021). Support for the conservation of interactions in the GA/DELLA pathway is also found in many other species such as tomato, in which SlBES1.8 represses the production of two GA-inactivating enzymes to increase GA levels and control leaf morphology (Su et al, 2022). This process is counteracted by the single DELLA protein in tomato, PROCERA (PRO), which interacts with SlBES1.8 to inhibit its transcriptional repressor capacity (Su et al, 2022).…”
Section: Swi/snf Pathwaymentioning
confidence: 84%
“…Already before the emergence of canonical GA signaling in vascular plants, DELLA proteins played a crucial role in plant development as seen in the liverwort Marchantia polymorpha, in which overexpression of MpDELLA leads to reduced plant growth (Hern andez-Garc ıa et al, 2021). Support for the conservation of interactions in the GA/DELLA pathway is also found in many other species such as tomato, in which SlBES1.8 represses the production of two GA-inactivating enzymes to increase GA levels and control leaf morphology (Su et al, 2022). This process is counteracted by the single DELLA protein in tomato, PROCERA (PRO), which interacts with SlBES1.8 to inhibit its transcriptional repressor capacity (Su et al, 2022).…”
Section: Swi/snf Pathwaymentioning
confidence: 84%
“…Tomato has been used as a model species to study compound leaf development for decades and some progress has been achieved. Hormones are key factors regulating compound leaf development, and numerous studies have shown that GAs promote leaf differentiation, decreasing leaf complexity in tomato ( Jasinski et al., 2008 ; Israeli et al., 2021 ; Su et al., 2022 ). For example, application of exogenous GAs or mutation of PROCERA / DELLA reduces the number of leaflets and makes leaf margins smoother and petioles longer ( Jasinski et al., 2008 ; Fleishon et al., 2011 ; Yanai et al., 2011 ).…”
Section: Vegetative Growthmentioning
confidence: 99%
“…Auxins and brassinosteroids (BRs) can also coordinate with GAs, regulating compound leaf development in tomato. SlBES1.8, a key regulator of BR signaling, directly represses SlGA2ox2 , SlGA2ox6 and SlGID1b-1 , influencing leaf morphogenesis ( Su et al., 2022 ). Moreover, the specific molecular mechanism underlying compound leaf development may be different among different species ( Bar and Ori, 2015 ).…”
Section: Vegetative Growthmentioning
confidence: 99%
“…Tomato is a fruit crop with high economic relevance and serves as a model organism for biologists that study fleshy fruit development and cold stress responses of chilling-sensitive plants. Several factors of BR biosynthesis and signaling have been identified in tomato, including the BR biosynthetic enzymes SlCPD and SlDWF4, and the BR signaling components SlBRI1, SlBES1, SlBZR1, and SlBIM1 (Bishop et al, 1999;Koka et al, 2000;Holton et al, 2007;Jia et al, 2021;Mori et al, 2021;Su et al, 2022). Overexpression of SlBRI1 promoted germination, growth of vegetative and reproductive organs and over-all fruit yield in tomato (Nie et al, 2017;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%